Pharmacist’s Use of Screening Tools to Estimate Risk of CVD: A Review of the Literature - Dónal Og O'Donovan; Stephen Byrne; Laura J. Sahm (Pharmacy, 2014)
To review pharmacist-led screening programmes for estimation of cardiovascular disease (CVD) risk using validated screening tools, studies were identified using a search of the following electronic databases: PubMed, EMBASE, Web of Knowledge and the Cochrane library databases. Each database was searched from inception to December 2011. The search terms used were: “cardiovascular disease”, “screening”, “risk estimation”, “pharmacist” and “pharmacy”. Titles, abstracts and full manuscripts were screened to determine eligibility. Inclusion criteria were: (i) Pharmacist-led CVD screening; and (ii) Use of validated screening tool or tools for CVD. From each included study information was collected on the following: Study author; year of publication; setting; inclusion and exclusion criteria; tools used and outcomes measured. Articles were grouped and independently verified to ensure they met with the inclusion criteria. Over 7,000 citations were found. Twenty full-length articles were retrieved for analysis, of which twelve were excluded, as they did not meet the inclusion criteria. The eight remaining articles were included in this literature review. Whilst pharmacists undertake screening in their own practice, this approach will only go so far. To have a population-health impact, pharmacists should be involved in proactive screening in a variety of settings.